Fix—do not ditch—the fundamental niche - Brian J. McGill; Daniel C. Laughlin (Trends in Ecology & Evolution, 2026)

Trait space and compactness: A new perspective on explaining variations in primary productivity - Jiahui Zhang; Kailiang Yu; Markus Reichstein; Li Xu; Ian J. Wright; Mirco Migliavacca; Ulisse Gomarasca; Daniel C. Laughlin; Xiaoyu Cen; Congcong Liu; Honglin He; Nianpeng He (Ecology, 2026)
A fundamental question in ecology is why plant communities have large trait space yet strong coordination among those traits across large scales, despite these patterns seeming contradictory. Answering this question requires quantitatively linking the geographic distribution of trait space and coordination with gross primary productivity (GPP). We leveraged an unprecedented large‐scale dataset of nine leaf traits for 5718 species‐site combinations with simultaneous field measurements of plant community composition in 64 naturally assembled communities to investigate trait spaces (hypervolume, quantity dimension) and trait compactness (coordination, efficiency dimension) and their influence on GPP. Trait space and compactness combined explained 72% of the variation of GPP. Interestingly, a larger trait space (more diverse trait combinations) drove higher GPP in resource‐poor communities, while higher trait compactness (greater coordination of traits) determined higher GPP in resource‐rich communities. Our findings provide a new perspective that natural plant communities increase both trait space and compactness to improve GPP, shedding light on the development of multidimensional functional ecology.

Divergent responses of seed banks and aboveground vegetation to drought and deluge in grasslands across an elevational gradient - Jennifer R. Gremer; Margaret M. Moore; Daniel C. Laughlin; Seth M. Munson (Oecologia, 2025)

Belowground persistence types relevant to severe disturbance - Jitka Klimešová; Daniel C. Laughlin; Frances Siebert; Joana Bergmann; Shersingh Joseph Tumber-Dávila; Karl Andraczek; Aline B. Bombo; Helge Bruelheide; Ying Fan; Grégoire T. Freschet; Justus Hennecke; Cody Coyotee Howard; et al. (Trends in Plant Science, 2025)

Fine-root traits coordinate with aboveground strategies yet poorly predict species’ response to spruce mortality - Trevor A. Carter; Alice E. Stears; Paula J. Fornwalt; David H. Atkins; Kathleen A. Dwire; Jesse R. Fleri; Katherine R. Hayes; Hailey E. Mount; Erin M. Twaddell; Sienna A. Wessel; Brian Buma; Daniel C. Laughlin (Plant and Soil, 2025)

Using Plant Invasions to Compare Occurrence‐ and Abundance‐Based Calculations of Biotic Homogenisation: Are Results Complementary or Contradictory? - D. M. Buonaiuto; David Barnett; Dana M. Blumenthal; Andrea N. Nebhut; Ian S. Pearse; Helen R. Sofaer; Cascade J. B. Sorte; Jeffrey D. Corbin; Regan Early; Magda Garbowski; Ines Ibanez; Daniel C. Laughlin; et al. (Global Ecology and Biogeography, 2025)
Aim Beta diversity quantifies the similarity of ecological assemblages. Its increase, known as biotic homogenisation, can be a consequence of biological invasions. However, species occurrence (presence/absence) and abundance‐based analyses can produce contradictory assessments of the magnitude and direction of changes in beta diversity. Previous work indicates these contradictions should be less frequent in nature than in theory, but a growing number of empirical studies report discrepancies between occurrence‐ and abundance‐based approaches. Understanding if these discrepancies represent a few isolated cases or are systematic across a diversity of ecosystems would allow us to better understand the general patterns, mechanisms and impacts of biotic homogenisation. Location United States. Time Period 1963–2020. Major Taxa Studied Vascular plants. Methods We used a dataset of more than 70,000 vegetation survey plots to assess differences in biotic homogenisation with and without invasion using both occurrence‐ and abundance‐based metrics of beta diversity. We estimated taxonomic biotic homogenisation by comparing beta diversity of invaded and uninvaded plots with both classes of metrics and investigated the characteristics of the non‐native species pool that influenced the likelihood that these metrics disagree. Results In 78% of plot comparisons, occurrence‐ and abundance‐based calculations agreed in direction, and the two metrics were generally well correlated. Our empirical results are consistent with previous theory. Discrepancies between the metrics were more likely when the same non‐native species was at high cover at both plots compared for beta diversity, and when these plots were spatially distant. Main Conclusions In about 20% of cases, our calculations revealed differences in direction (homogenisation vs. differentiation) when comparing occurrence‐ and abundance‐based metrics, indicating that the metrics are not interchangeable, especially when distances between plots are high and invader diversity is low. When data permit, combining the two approaches can offer insights into the role of invasions and extirpations in driving biotic homogenisation/differentiation.

The mouse metabolic phenotyping center (MMPC) live consortium: an NIH resource for in vivo characterization of mouse models of diabetes and obesity - Maren Laughlin; Richard McIndoe; Sean H. Adams; Renee Araiza; Julio E. Ayala; Lucy Kennedy; Louise Lanoue; Louise Lantier; James Macy; Eann Malabanan; Owen P. McGuinness; Rachel Perry; et al. (Mammalian Genome, 2024)
The Mouse Metabolic Phenotyping Center (MMPC) Live Program was established in 2023 by the National Institute for Diabetes, Digestive and Kidney Diseases (NIDDK) at the National Institutes of Health (NIH) to advance biomedical research by providing the scientific community with standardized, high quality phenotyping services for mouse models of diabetes and obesity. Emerging as the next iteration of the MMPC Program which served the biomedical research community for 20 years (2001–2021), MMPC Live is designed as an outwardly-facing consortium of service cores that collaborate to provide reduced-cost consultation and metabolic, physiologic, and behavioral phenotyping tests on live mice for U.S. biomedical researchers. Four MMPC Live Centers located at universities around the country perform complex and often unique procedures in vivo on a fee for service basis, typically on mice shipped from the client or directly from a repository or vendor. Current areas of expertise include energy balance and body composition, insulin action and secretion, whole body carbohydrate and lipid metabolism, cardiovascular and renal function, food intake and behavior, microbiome and xenometabolism, and metabolic pathway kinetics. Additionally, an opportunity arose to reduce barriers to access and expand the diversity of the biomedical research workforce by establishing the VIBRANT Program. Directed at researchers historically underrepresented in the biomedical sciences, VIBRANT-eligible investigators have access to testing services, travel and career development awards, expert advice and experimental design consultation, and short internships to learn test technologies. Data derived from experiments run by the Centers belongs to the researchers submitting mice for testing which can be made publicly available and accessible from the MMPC Live database following publication. In addition to services, MMPC Live staff provide expertise and advice to researchers, develop and refine test protocols, engage in outreach activities, publish scientific and technical papers, and conduct educational workshops and training sessions to aid researchers in unraveling the heterogeneity of diabetes and obesity.

Environmental filtering of regeneration patterns in a forest dynamic mosaic in south-central Chile - Christopher H. Lusk; Susana Paula; Daniel C. Laughlin; Rocio Fritz; Luisa Parra-Darmendrail (Perspectives in Plant Ecology, Evolution and Systematics, 2024)

Patterns and drivers of early conifer regeneration following stand-replacing wildfire in Pacific Northwest (USA) temperate maritime forests - Madison M. Laughlin; Liliana K. Rangel-Parra; Jenna E. Morris; Daniel C. Donato; Joshua S. Halofsky; Brian J. Harvey (Forest Ecology and Management, 2023)

Water availability dictates how plant traits predict demographic rates - Alice E. Stears; Peter B. Adler; Dana M. Blumenthal; Julie A. Kray; Kevin E. Mueller; Troy W. Ocheltree; Kevin R. Wilcox; Daniel C. Laughlin (Ecology, 2022)
A major goal in ecology is to make generalizable predictions of organism responses to environmental variation based on their traits. However, straightforward relationships between traits and fitness are rare and likely to vary with environmental context. Characterizing how traits mediate demographic responses to the environment may enhance the predictions of organism responses to global change. We synthesized 15 years of demographic data and species‐level traits in a shortgrass steppe to determine whether the effects of leaf and root traits on growth and survival depended on seasonal water availability. We predicted that (1) species with drought‐tolerant traits, such as lower leaf turgor loss point (TLP) and higher leaf and root dry matter content (LDMC and RDMC), would be more likely to survive and grow in drier years due to higher wilting resistance, (2) these traits would not predict fitness in wetter years, and (3) traits that more directly measure physiological mechanisms of water use such as TLP would best predict demographic responses. We found that graminoids with more negative TLP and higher LDMC and RDMC had higher survival rates in drier years. Forbs demonstrated similar yet more variable responses. Graminoids grew larger in wetter years, regardless of traits. However, in both wet and dry years, graminoids with more negative TLP and higher LDMC and RDMC grew larger than less negative TLP and low LDMC and RDMC species. Traits significantly mediated the impact of drought on survival, but not growth, suggesting that survival could be a stronger driver of species' drought response in this system. TLP predicted survival in drier years, but easier to measure LDMC and RDMC were equal or better predictors. These results advance our understanding of the mechanisms by which drought drives population dynamics, and show that abiotic context determines how traits drive fitness.

Predictions of biodiversity are improved by integrating trait‐based competition with abiotic filtering - Loïc Chalmandrier; Daniel B. Stouffer; Adam S. T. Purcell; William G. Lee; Andrew J. Tanentzap; Daniel C. Laughlin (Ecology Letters, 2022)
All organisms must simultaneously tolerate the environment and access limiting resources if they are to persist. Approaches to understanding abiotic filtering and competitive interactions have generally been developed independently. Consequently, integrating those factors to predict species abundances and community structure remains an unresolved challenge. We introduce a new synthetic framework that models both abiotic filtering and competition by using functional traits. First, our framework estimates species carrying capacities along abiotic gradients. Second, it estimates pairwise competitive interactions as a function of species trait differences. Applied to the study of a complex wetland community, our combined approach more than doubles the explained variance of species abundances compared to a model of abiotic tolerances alone. Trait‐based integration of competitive interactions and abiotic filtering improves our ability to predict species abundances, bringing us closer to more accurate predictions of biodiversity structure in a changing world.

Cover and density of southwestern ponderosa pine understory plants in permanent chart quadrats (2002–2020) - Margaret M. Moore; Jeffrey S. Jenness; Daniel C. Laughlin; Robert T. Strahan; Jonathan D. Bakker; Helen E. Dowling; Judith D. Springer (Ecology, 2022)
This data set consists of 101 permanent 1 m × 1 m (1‐m 2 ) quadrats located within southwestern ponderosa pine ecosystems near Flagstaff, Arizona, USA. Individual plants in these quadrats were identified and mapped annually for 19 years (2002–2020). The original chart quadrats were established between 1912 and 1927 to determine the effects of domestic livestock grazing on herbaceous plants and pine seedlings. Today these data provide opportunities to examine the effects of climate and land‐use change on plant demography, population dynamics, and community processes. We provide the following data and data formats: (1) digitized maps of all plant locations in shapefile and geodatabase format, (2) shapefiles showing annual locations of each individual plant species, (3) annual maps of each quadrat in TIFF and PDF format, (4) annual basal area of each species per quadrat for species mapped as polygons, (5) tabular representation of polygon areas and centroid locations for plant species mapped as polygons, (6) tabular representation of point locations for plant species mapped as points, (7) plot‐scale 20 m × 20 m overstory tree canopy cover, tree basal area, parent material, and elevation, (8) quadrat‐scale information (e.g., quadrat site and number, coordinates in UTM Zone 12 and latitude/longitude, and descriptive comments for each quadrat), (9) plant species list, (10) summary of plant species observed in each quadrat, (11) summary of quadrats mapped by site and year, and (12) data formatted for use in Integral Projection Models (IPM) and plant population analyses. There are no copyright restrictions; please cite this paper and the associated data set when data are used in publications.

Environmental filters of freshwater fish community assembly along elevation and latitudinal gradients - Mark A. Kirk; Frank J. Rahel; Daniel C. Laughlin (Global Ecology and Biogeography, 2022)
Aim The aim was to identify drivers of historical freshwater fish community assembly by testing for interactions between functional traits and two climatic gradients, namely elevation and latitude. Many studies conclude that environmental filtering is the dominant process of community‐wide trait convergence at high elevations and high latitudes, but a full understanding of which specific filters cause trait convergence is lacking. Location Great Plains–Rocky Mountains, USA. Time period 1960–2018. Major taxa studied Freshwater fish. Methods Using 2,539 stream fish community surveys documenting the native distributions of 51 species, we evaluated trait–environment relationships (trade‐offs) and trait–dispersion relationships (standardized effect sizes from null models) along elevation and latitudinal gradients in four functional trait categories. We tested whether elevation and latitude exhibited similar trait–environment and trait–dispersion relationships using four functional trait categories (life history, habitat, trophic and locomotion). We predicted that elevation and latitude would have similar relationships owing to shared environmental filters of cold stress and dispersal constraints. Results Life history was the only trait category to display evidence of increased environmental filtering along both gradients, with trait dispersion more constrained at high elevations and high latitudes. Trade‐offs revealed that periodic strategies (high fecundity, low juvenile survivorship) decreased with elevation and increased with latitude, whereas equilibrium strategies (low fecundity, high juvenile survivorship) declined along both gradients. Despite the observation of predictable trade‐offs for habitat, trophic and locomotion trait strategies, there was little evidence for environmental filtering of these traits at high elevations and high latitudes. Main conclusions Elevation and latitude appear to be environmental filters of freshwater fish community assembly when mediated through life‐history strategies, which is likely to be attributable to thermal constraints on growth and reproduction. Our results support the role of environmental filtering in trait convergence patterns along climatic gradients, and we identify cold stress as one specific filter of community assembly.

Global root traits (GRooT) database - Nathaly R. Guerrero‐Ramírez; Liesje Mommer; Grégoire T. Freschet; Colleen M. Iversen; M. Luke McCormack; Jens Kattge; Hendrik Poorter; Fons van der Plas; Joana Bergmann; Thom W. Kuyper; Larry M. York; Helge Bruelheide; et al. (Global Ecology and Biogeography, 2021)
Motivation Trait data are fundamental to the quantitative description of plant form and function. Although root traits capture key dimensions related to plant responses to changing environmental conditions and effects on ecosystem processes, they have rarely been included in large‐scale comparative studies and global models. For instance, root traits remain absent from nearly all studies that define the global spectrum of plant form and function. Thus, to overcome conceptual and methodological roadblocks preventing a widespread integration of root trait data into large‐scale analyses we created the Global Root Trait (GRooT) Database. GRooT provides ready‐to‐use data by combining the expertise of root ecologists with data mobilization and curation. Specifically, we (a) determined a set of core root traits relevant to the description of plant form and function based on an assessment by experts, (b) maximized species coverage through data standardization within and among traits, and (c) implemented data quality checks. Main types of variables contained GRooT contains 114,222 trait records on 38 continuous root traits. Spatial location and grain Global coverage with data from arid, continental, polar, temperate and tropical biomes. Data on root traits were derived from experimental studies and field studies. Time period and grain Data were recorded between 1911 and 2019. Major taxa and level of measurement GRooT includes root trait data for which taxonomic information is available. Trait records vary in their taxonomic resolution, with subspecies or varieties being the highest and genera the lowest taxonomic resolution available. It contains information for 184 subspecies or varieties, 6,214 species, 1,967 genera and 254 families. Owing to variation in data sources, trait records in the database include both individual observations and mean values. Software format GRooT includes two csv files. A GitHub repository contains the csv files and a script in R to query the database.

Assessing the reliability of predicted plant trait distributions at the global scale - Coline C. F. Boonman; Ana Benítez‐López; Aafke M. Schipper; Wilfried Thuiller; Madhur Anand; Bruno E. L. Cerabolini; Johannes H. C. Cornelissen; Andres Gonzalez‐Melo; Wesley N. Hattingh; Pedro Higuchi; Daniel C. Laughlin; Vladimir G. Onipchenko; et al. (Global Ecology and Biogeography, 2020)
Aim Predictions of plant traits over space and time are increasingly used to improve our understanding of plant community responses to global environmental change. A necessary step forward is to assess the reliability of global trait predictions. In this study, we predict community mean plant traits at the global scale and present a systematic evaluation of their reliability in terms of the accuracy of the models, ecological realism and various sources of uncertainty. Location Global. Time period Present. Major taxa studied Vascular plants. Methods We predicted global distributions of community mean specific leaf area, leaf nitrogen concentration, plant height and wood density with an ensemble modelling approach based on georeferenced, locally measured trait data representative of the plant community. We assessed the predictive performance of the models, the plausibility of predicted trait combinations, the influence of data quality, and the uncertainty across geographical space attributed to spatial extrapolation and diverging model predictions. Results Ensemble predictions of community mean plant height, specific leaf area and wood density resulted in ecologically plausible trait–environment relationships and trait–trait combinations. Leaf nitrogen concentration, however, could not be predicted reliably. The ensemble approach was better at predicting community trait means than any of the individual modelling techniques, which varied greatly in predictive performance and led to divergent predictions, mostly in African deserts and the Arctic, where predictions were also extrapolated. High data quality (i.e., including intraspecific variability and a representative species sample) increased model performance by 28%. Main conclusions Plant community traits can be predicted reliably at the global scale when using an ensemble approach and high‐quality data for traits that mostly respond to large‐scale environmental factors. We recommend applying ensemble forecasting to account for model uncertainty, using representative trait data, and more routinely assessing the reliability of trait predictions.

Alternative designs and tropical tree seedling growth performance landscapes - Samantha J. Worthy; Daniel C. Laughlin; Jenny Zambrano; María N. Umaña; Caicai Zhang; Luxiang Lin; Min Cao; Nathan G. Swenson (Ecology, 2020)
The functional trait values that constitute a whole‐plant phenotype interact with the environment to determine demographic rates. Current approaches often fail to explicitly consider trait × trait and trait × environment interactions, which may lead to missed information that is valuable for understanding and predicting the drivers of demographic rates and functional diversity. Here, we consider these interactions by modeling growth performance landscapes that span multidimensional trait spaces along environmental gradients. We utilize individual‐level leaf, stem, and root trait data combined with growth data from tree seedlings along soil nutrient and light gradients in a hyper‐diverse tropical rainforest. We find that multiple trait combinations in phenotypic space (i.e., alternative designs) lead to multiple growth performance peaks that shift along light and soil axes such that no single or set of interacting traits consistently results in peak growth performance. Evidence from these growth performance peaks also generally indicates frequent independence of above‐ and belowground resource acquisition strategies. These results help explain how functional diversity is maintained in ecological communities and question the practice of utilizing a single trait or environmental variable, in isolation, to predict the growth performance of individual trees.

TRY plant trait database – enhanced coverage and open access - Jens Kattge; Gerhard Bönisch; Sandra Díaz; Sandra Lavorel; Iain Colin Prentice; Paul Leadley; Susanne Tautenhahn; Gijsbert D. A. Werner; Tuomas Aakala; Mehdi Abedi; Alicia T. R. Acosta; George C. Adamidis; et al. (Global Change Biology, 2020)
Plant traits—the morphological, anatomical, physiological, biochemical and phenological characteristics of plants—determine how plants respond to environmental factors, affect other trophic levels, and influence ecosystem properties and their benefits and detriments to people. Plant trait data thus represent the basis for a vast area of research spanning from evolutionary biology, community and functional ecology, to biodiversity conservation, ecosystem and landscape management, restoration, biogeography and earth system modelling. Since its foundation in 2007, the TRY database of plant traits has grown continuously. It now provides unprecedented data coverage under an open access data policy and is the main plant trait database used by the research community worldwide. Increasingly, the TRY database also supports new frontiers of trait‐based plant research, including the identification of data gaps and the subsequent mobilization or measurement of new data. To support this development, in this article we evaluate the extent of the trait data compiled in TRY and analyse emerging patterns of data coverage and representativeness. Best species coverage is achieved for categorical traits—almost complete coverage for ‘plant growth form’. However, most traits relevant for ecology and vegetation modelling are characterized by continuous intraspecific variation and trait–environmental relationships. These traits have to be measured on individual plants in their respective environment. Despite unprecedented data coverage, we observe a humbling lack of completeness and representativeness of these continuous traits in many aspects. We, therefore, conclude that reducing data gaps and biases in the TRY database remains a key challenge and requires a coordinated approach to data mobilization and trait measurements. This can only be achieved in collaboration with other initiatives.

Long‐term changes in the water quality of a deep temperate oligotrophic lake in response to catchment disturbance: evidence from sediment cores - Alfred Theodore N. K. Kpodonu; David P. Hamilton; Christopher H. Lusk; Adam Hartland; Daniel C. Laughlin; Piet Verburg (New Zealand Journal of Marine and Freshwater Research, 2019)
This study examined long‐term stability in water quality of Lake Okataina, North Island, New Zealand, inferred from sediments deposited from 1836 to 2009, during which time there was a pyroclastic volcanic eruption (Tarawera 1886) and successive introductions of invasive mammals. Multiple geochemical proxies were analysed stratigraphically for organic matter loading, primary productivity, redox potential and phosphorus retention capacity. Organic matter loading to the lake is mostly authochthonous (algae) although there was increased allochthonous (terrestrial) loading immediately after the Tarawera eruption. After 1920, there was a sustained increase in inorganic erosion flux. Primary productivity appeared to increase considerably about 1960, but has remained relatively unchanged more recently. Our results suggest that the lake could recover from the impact of the volcanic eruption within a few decades, but the introduction of mammals may affect its resilience and lead to more pervasive impacts on the biogeochemistry.

Robustness of trait connections across environmental gradients and growth forms - Habacuc Flores‐Moreno; Farideh Fazayeli; Arindam Banerjee; Abhirup Datta; Jens Kattge; Ethan E. Butler; Owen K. Atkin; Kirk Wythers; Ming Chen; Madhur Anand; Michael Bahn; Chaeho Byun; et al. (Global Ecology and Biogeography, 2019)
Aim Plant trait databases often contain traits that are correlated, but for whom direct (undirected statistical dependency) and indirect (mediated by other traits) connections may be confounded. The confounding of correlation and connection hinders our understanding of plant strategies, and how these vary among growth forms and climate zones. We identified the direct and indirect connections across plant traits relevant to competition, resource acquisition and reproductive strategies using a global database and explored whether connections within and between traits from different tissue types vary across climates and growth forms. Location Global. Major taxa studied Plants. Time period Present. Methods We used probabilistic graphical models and a database of 10 plant traits (leaf area, specific leaf area, mass‐ and area‐based leaf nitrogen and phosphorous content, leaf life span, plant height, stem specific density and seed mass) with 16,281 records to describe direct and indirect connections across woody and non‐woody plants across tropical, temperate, arid, cold and polar regions. Results Trait networks based on direct connections are sparser than those based on correlations. Land plants had high connectivity across traits within and between tissue types; leaf life span and stem specific density shared direct connections with all other traits. For both growth forms, two groups of traits form modules of more highly connected traits; one related to resource acquisition, the other to plant architecture and reproduction. Woody species had higher trait network modularity in polar compared to temperate and tropical climates, while non‐woody species did not show significant differences in modularity across climate regions. Main conclusions Plant traits are highly connected both within and across tissue types, yet traits segregate into persistent modules of traits. Variation in the modularity of trait networks suggests that trait connectivity is shaped by prevailing environmental conditions and demonstrates that plants of different growth forms use alternative strategies to cope with local conditions.

Fine Root Traits Are Correlated with Flooding Duration while Aboveground Traits Are Related to Grazing in an Ephemeral Wetland - Adam S. T. Purcell; William G. Lee; Andrew J. Tanentzap; Daniel C. Laughlin (Wetlands, 2019)

Niche opportunities for invasive annual plants in dryland ecosystems are controlled by disturbance, trophic interactions, and rainfall - Richard A. Gill; Rory C. O’Connor; Aaron Rhodes; Tara B. B. Bishop; Daniel C. Laughlin; Samuel B. St. Clair (Oecologia, 2018)

Survival rates indicate that correlations between community‐weighted mean traits and environments can be unreliable estimates of the adaptive value of traits - Daniel C. Laughlin; Robert T. Strahan; Peter B. Adler; Margaret M. Moore (Ecology Letters, 2018)
Correlations between community‐weighted mean ( CWM ) traits and environmental gradients are often assumed to quantify the adaptive value of traits. We tested this assumption by comparing these correlations with models of survival probability using 46 perennial species from long‐term permanent plots in pine forests of Arizona. Survival was modelled as a function of trait × environment interactions, plant size, climatic variation and neighbourhood competition. The effect of traits on survival depended on the environmental conditions, but the two statistical approaches were inconsistent. For example, CWM ‐specific leaf area ( SLA ) and soil fertility were uncorrelated. However, survival was highest for species with low SLA in infertile soil, a result which agreed with expectations derived from the physiological trade‐off underpinning leaf economic theory. CWM trait–environment relationships were unreliable estimates of how traits affected survival, and should only be used in predictive models when there is empirical support for an evolutionary trade‐off that affects vital rates.

Root nutrient concentration and biomass allocation are more plastic than morphological traits in response to nutrient limitation - Kris R. Kramer-Walter; Daniel C. Laughlin (Plant and Soil, 2017)

Constraints on trait combinations explain climatic drivers of biodiversity: the importance of trait covariance in community assembly - John M. Dwyer; Daniel C. Laughlin (Ecology Letters, 2017)
Trade‐offs maintain diversity and structure communities along environmental gradients. Theory indicates that if covariance among functional traits sets a limit on the number of viable trait combinations in a given environment, then communities with strong multidimensional trait constraints should exhibit low species diversity. We tested this prediction in winter annual plant assemblages along an aridity gradient using multilevel structural equation modelling. Univariate and multivariate functional diversity measures were poorly explained by aridity, and were surprisingly poor predictors of community richness. By contrast, the covariance between maximum height and seed mass strengthened along the aridity gradient, and was strongly associated with richness declines. Community richness had a positive effect on local neighbourhood richness, indicating that climate effects on trait covariance indirectly influence diversity at local scales. We present clear empirical evidence that declines in species richness along gradients of environmental stress can be due to increasing constraints on multidimensional phenotypes.

Tree mortality across biomes is promoted by drought intensity, lower wood density and higher specific leaf area - Sarah Greenwood; Paloma Ruiz‐Benito; Jordi Martínez‐Vilalta; Francisco Lloret; Thomas Kitzberger; Craig D. Allen; Rod Fensham; Daniel C. Laughlin; Jens Kattge; Gerhard Bönisch; Nathan J. B. Kraft; Alistair S. Jump (Ecology Letters, 2017)
Drought events are increasing globally, and reports of consequent forest mortality are widespread. However, due to a lack of a quantitative global synthesis, it is still not clear whether drought‐induced mortality rates differ among global biomes and whether functional traits influence the risk of drought‐induced mortality. To address these uncertainties, we performed a global meta‐analysis of 58 studies of drought‐induced forest mortality. Mortality rates were modelled as a function of drought, temperature, biomes, phylogenetic and functional groups and functional traits. We identified a consistent global‐scale response, where mortality increased with drought severity [log mortality (trees trees −1 year −1 ) increased 0.46 (95% CI = 0.2–0.7) with one SPEI unit drought intensity]. We found no significant differences in the magnitude of the response depending on forest biomes or between angiosperms and gymnosperms or evergreen and deciduous tree species. Functional traits explained some of the variation in drought responses between species (i.e. increased from 30 to 37% when wood density and specific leaf area were included). Tree species with denser wood and lower specific leaf area showed lower mortality responses. Our results illustrate the value of functional traits for understanding patterns of drought‐induced tree mortality and suggest that mortality could become increasingly widespread in the future.

Herbicide application during pasture renewal initially increases root turnover and carbon input to soil in perennial ryegrass and white clover pasture - Samuel R. McNally; Daniel C. Laughlin; Susanna Rutledge; Mike B. Dodd; Johan Six; Louis A. Schipper (Plant and Soil, 2017)

Soil–climate interactions explain variation in foliar, stem, root and reproductive traits across temperate forests - Angela H. Simpson; Sarah J. Richardson; Daniel C. Laughlin (Global Ecology and Biogeography, 2016)
Aim The individual effects of climate and soil properties on functional trait distributions have become increasingly clear with recent syntheses of large datasets. However, the distribution of traits in a given climate may depend on the fertility of the soil. Our aim was to quantify how soil–climate interactions explain community‐level variation in functional traits from every plant organ to improve predictions of plant community responses to environmental change. Location Temperate forests throughout New Zealand. Methods We measured traits of foliar, stem, root and reproductive tissue for 64 species and calculated abundance‐weighted mean trait values on 324 forest plots. Multiple linear regression was used to model the variation in each of the traits as functions of mean annual temperature (MAT), vapour pressure deficit (VPD), soil pH, soil total phosphorus (P) and their interactions. Results Soil–climate interactions explained significant variation in functional traits. For example, specific leaf area (SLA) was highest in high‐P soil within a wet and warm climate; however, strong interactions indicate that SLA was lowest in wet and warm climates in low‐P soil. Root tissue density was lowest in warm climates and high‐P soil, but it was high in warm climates and low‐P soil and in cold climates and high‐P soil. According to model predictions, the largest potential responses of vegetation to warming may occur in fertile and wet environments. Main conclusions Pervasive soil–climate interactions demonstrate that interpreting simple bivariate relationships between traits and climate must be done with caution because the adaptive value of traits in a given climate depends on the fertility of the soil. Predictions of vegetation responses to climate change will improve significantly by incorporating local‐scale soil properties into modelling frameworks. Rising global temperatures may shift community‐level trait values in opposite directions depending on whether the soil is fertile or infertile.

Reinforcing loose foundation stones in trait-based plant ecology - Bill Shipley; Francesco De Bello; J. Hans C. Cornelissen; Etienne Laliberté; Daniel C. Laughlin; Peter B. Reich (Oecologia, 2016)

Environmental Filtering and Positive Plant Litter Feedback Simultaneously Explain Correlations Between Leaf Traits and Soil Fertility - Daniel C. Laughlin; Sarah J. Richardson; Elaine F. Wright; Peter J. Bellingham (Ecosystems, 2015)

Root carbon inputs under moderately diverse sward and conventional ryegrass-clover pasture: implications for soil carbon sequestration - Samuel Rae McNally; Daniel C. Laughlin; Susanna Rutledge; Mike B. Dodd; Johan Six; Louis A. Schipper (Plant and Soil, 2015)

Applying trait‐based models to achieve functional targets for theory‐driven ecological restoration - Daniel C. Laughlin (Ecology Letters, 2014)
Manipulating community assemblages to achieve functional targets is a key component of restoring degraded ecosystems. The response‐and‐effect trait framework provides a conceptual foundation for translating restoration goals into functional trait targets, but a quantitative framework has been lacking for translating trait targets into assemblages of species that practitioners can actually manipulate. This study describes new trait‐based models that can be used to generate ranges of species abundances to test theories about which traits, which trait values and which species assemblages are most effective for achieving functional outcomes. These models are generalisable, flexible tools that can be widely applied across many terrestrial ecosystems. Examples illustrate how the framework generates assemblages of indigenous species to (1) achieve desired community responses by applying the theories of environmental filtering, limiting similarity and competitive hierarchies, or (2) achieve desired effects on ecosystem functions by applying the theories of mass ratios and niche complementarity. Experimental applications of this framework will advance our understanding of how to set functional trait targets to achieve the desired restoration goals. A trait‐based framework provides restoration ecology with a robust scaffold on which to apply fundamental ecological theory to maintain resilient and functioning ecosystems in a rapidly changing world.

Accuracy assessment of land surface temperature retrievals from Landsat 7 ETM + in the Dry Valleys of Antarctica using iButton temperature loggers and weather station data - Lars Brabyn; Peyman Zawar-Reza; Glen Stichbury; Craig Cary; Bryan Storey; Daniel C. Laughlin; Marwan Katurji (Environmental Monitoring and Assessment, 2014)

Topical gradients in plant ecology - Daniel C. Laughlin (Plant Ecology, 2012)

A predictive model of community assembly that incorporates intraspecific trait variation - Daniel C. Laughlin; Chaitanya Joshi; Peter M. van Bodegom; Zachary A. Bastow; Peter Z. Fulé (Ecology Letters, 2012)
Community assembly involves two antagonistic processes that select functional traits in opposite directions. Environmental filtering tends to increase the functional similarity of species within communities leading to trait convergence, whereas competition tends to limit the functional similarity of species within communities leading to trait divergence. Here, we introduce a new hierarchical B ayesian model that incorporates intraspecific trait variation into a predictive framework to unify classic coexistence theory and evolutionary biology with recent trait‐based approaches. Model predictions exhibited a significant positive correlation ( r = 0.66) with observed relative abundances along a 10 °C gradient in mean annual temperature. The model predicted the correct dominant species in half of the plots, and accurately reproduced species' temperature optimums. The framework is generalizable to any ecosystem as it can accommodate any species pool, any set of functional traits and multiple environmental gradients, and it eliminates some of the criticisms associated with recent trait‐based community assembly models.

Evidence for indirect effects of plant diversity and composition on net nitrification - Daniel C. Laughlin; Stephen C. Hart; Jason P. Kaye; Margaret M. Moore (Plant and Soil, 2010)

Restoring plant species diversity and community composition in a ponderosa pine-bunchgrass ecosystem - Daniel C. Laughlin; Jonathan D. Bakker; Mark L. Daniels; Margaret M. Moore; Cheryl A. Casey; Judith D. Springer (Plant Ecology, 2008)

Understorey plant community structure in lower montane and subalpine forests, Grand Canyon National Park, USA - Daniel C. Laughlin; Jonathan D. Bakker; Peter Z. Fulé (Journal of Biogeography, 2005)
Aim Our objectives were to compare understorey plant community structure among forest types, and to test hypotheses relating understorey community structure within lower montane and subalpine forests to fire history, forest structure, fuel loads and topography. Location Forests on the North Rim of Grand Canyon National Park, Arizona, USA. Methods We measured understorey ( manova to assess compositional differences between forest types, and used indicator species analysis to identify species driving the differences between forest types. We then compiled sets of proposed models for predicting plant community structure, and used Akaike's information criterion (AIC C ) to determine the support for each model. Model averaging was used to make multi‐model inferences if no single model was supported. Results Within the lower montane zone, pine–oak forests had greater understorey plant cover, richness and diversity than pure stands of ponderosa pine ( Pinus ponderosa P. & C. Lawson var. scopulorum Engelm.). Plant cover was negatively related to time since fire and to ponderosa pine basal area, and was highest on northern slopes and where Gambel oak ( Quercus gambelii Nutt.) was present. Species richness was negatively related to time since fire and to ponderosa pine basal area, and was highest on southern slopes and where Gambel oak was present. Annual forb species richness was negatively related to time since fire. Community composition was related to time since fire, pine and oak basal area, and topography. Within subalpine forests, plant cover was negatively related to subalpine fir basal area and amounts of coarse woody debris (CWD), and positively related to Engelmann spruce basal area. Species richness was negatively related to subalpine fir basal area and amounts of CWD, was positively related to Engelmann spruce basal area, and was highest on southern slopes. Community composition was related to spruce, fir and aspen basal areas, amounts of CWD, and topography. Main conclusions In montane forests, low‐intensity surface fire is an important ecological process that maintains understorey communities within the range of natural variability and appears to promote landscape heterogeneity. The presence of Gambel oak was positively associated with high floristic diversity. Therefore management that encourages lightning‐initiated wildfires and Gambel oak production may promote floristic diversity. In subalpine forests, warm southern slopes and areas with low amounts of subalpine fir and CWD were positively associated with high floristic diversity. Therefore the reduction of CWD and forest densities through managed wildfire may promote floristic diversity, although fire use in subalpine forests is inherently more difficult due to intense fire behaviour in dense spruce–fir forests.